The α2C-adrenoceptor antagonist JP-1302 controls behavioral parameters, tyrosine hydroxylase activity and receptor expression in a rat model of ketamine-induced schizophrenia-like deficits - AKAKIN, DİLEK; GÖREN, MEHMET ZAFER (My University, 2022)
© 2022Schizophrenia is a chronic disabling disease affecting 1 % of the population. Current antipsychotics have limited efficacy in mitigating the severity of the symptoms of the disease. Therefore, searching for new therapeutic targets is essential. Previous studies have shown that α2C-adrenoceptor antagonists may have antipsychotic and pro-cognitive effects. Therefore, the current study evaluates the behavioral and neurochemical effects of JP-1302, a selective α2C-adrenoceptor antagonist, in a model of schizophrenia-like deficits induced by sub-chronic ketamine (KET) administration. Here, we administered ketamine (25 mg/kg, i.p.) to male and female Wistar rats for eight consecutive days. On the last two days of ketamine administration, rats were pretreated with either JP-1302 (1-3-10 μmol/kg, i.p.), chlorpromazine (0.1 mg/kg, i.p.), or saline, and the behavioral tests were performed. Behaviors related to positive (locomotor activity), negative (social interaction), and cognitive (novel object recognition) symptoms of schizophrenia were assessed. Glutamate, glutamine, GABA levels, and α2C-adrenoceptor expression were measured in the frontal cortex and the hippocampus. Tyrosine hydroxylase immunocytochemical reactivity was also shown in the midbrain regions. Sub-chronic ketamine administration increased locomotor activity and produced robust social interaction and object recognition deficits, and JP-1302 significantly ameliorated ketamine-induced cognitive deficits. Ketamine induced a hyperdopaminergic activity in the striatum, which was reversed by the treatment with JP-1302. Also, the α2C-adrenoceptor expression was higher in the frontal cortex and hippocampus in the ketamine-treated rats. Our findings confirm that α2C-adrenoceptor antagonism may be a potential drug target for treating cognitive disorders related to schizophrenia.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Sosyal ve Beşeri Bilimler; Psikoloji; Davranış Bilimleri; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Social Sciences and Humanities; Psychology; Behavioural Sciences; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Sinirbilim ve Davranış; Farmakoloji ve Toksikoloji; PSİKOLOJİ, BİYOLOJİK; DAVRANIŞ BİLİMLERİ; FARMAKOLOJİ VE ECZACILIK; TOKSİKOLOJİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); PSYCHOLOGY; NEUROSCIENCE & BEHAVIOR; PHARMACOLOGY & TOXICOLOGY; MOLECULAR BIOLOGY & GENETICS; PSYCHOLOGY, BIOLOGICAL; BEHAVIORAL SCIENCES; PHARMACOLOGY & PHARMACY; TOXICOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Biyokimya; Toksikoloji; Farmakoloji; Klinik Biyokimya; Biyolojik Psikiyatri; Davranışsal Sinirbilim; Biochemistry; Toxicology; Pharmacology; Clinical Biochemistry; Biological Psychiatry; Behavioral Neuroscience; HPLC; Novel object recognition; Schizophrenia; Western-blotting